The Effect of Social Media Marketing TikTok and Product Quality Towards Purchase Intention - Meliawati, Tiara; Gerald, Sweety Celendine; Aruman, Akhmad Edhy (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2023)
Social media has changed how companies and brands communicate with customers. To compete companies run social media marketing to obtain a competitive advantage. As a small and medium-sized company, Bittersweet by Najla utilizes social media marketing with TikTok and product quality to increase buying intention. This study aimed to determine the effect of social media marketing and product quality on purchase intention. The method used quantitative with a non-probability sampling technique, and questionnaires collected the data from 207 respondents. The analysis was carried out using the SEM-LISREL. The study results, first, social media marketing affects buying intention; second, product quality affects buying stake; and third, social media marketing and product quality are correlated with purchase intention. An indicator with the most significant value in social media marketing variables is TikTok, a brand that provides information search and services tailored to customer needs. In the product quality variable, one indicator has the most significant coefficient correlation value, namely the product's appearance. Therefore, Bittersweet by Najla continues to use TikTok as a social media platform for its marketing techniques and improve the quality of its products.